Harnessing the cGAS-STING pathway to potentiate radiation therapy: current approaches and future directions - Colangelo, Nicholas W.; Gerber, Naamit K.; Vatner, Ralph E.; Cooper, Benjamin T. (Frontiers in Pharmacology, 2024)
In this review, we cover the current understanding of how radiation therapy, which uses ionizing radiation to kill cancer cells, mediates an anti-tumor immune response through the cGAS-STING pathway, and how STING agonists might potentiate this. We examine how cGAS-STING signaling mediates the release of inflammatory cytokines in response to nuclear and mitochondrial DNA entering the cytoplasm. The significance of this in the context of cancer is explored, such as in response to cell-damaging therapies and genomic instability. The contribution of the immune and non-immune cells in the tumor microenvironment is considered. This review also discusses the burgeoning understanding of STING signaling that is independent of inflammatory cytokine release and the various mechanisms by which cancer cells can evade STING signaling. We review the available data on how ionizing radiation stimulates cGAS-STING signaling as well as how STING agonists may potentiate the anti-tumor immune response induced by ionizing radiation. There is also discussion of how novel radiation modalities may affect cGAS-STING signaling. We conclude with a discussion of ongoing and planned clinical trials combining radiation therapy with STING agonists, and provide insights to consider when planning future clinical trials combining these treatments.